Tuning the interlayer spacing of high-T_{c} Bi-based superconductors by intercalation: measuring the penetration depth and the two-dimensional superfluid density. - Baker, P; Lancaster, T; Blundell, S; Pratt, F; Brooks, M; Kwon, S (2009)
Substantial control of the interlayer spacing in Bi-based high temperature superconductors has been achieved through the intercalation of guest molecules between the superconducting layers. Measurements using implanted muons reveal that the penetration depth increases with increasing layer separation while T_{c} does not vary appreciably, demonstrating that the bulk superfluid density is not the determining factor controlling T_{c}. Our results strongly suggest that for Bi-based high temperature superconductors the superfluid density appearing in the Uemura scaling relation rho_{s} proportional, variantT_{c} should be interpreted as the two-dimensional density within the superconducting layers, which we find to be constant for each class of system investigated.